The ReFuGe 2020 Consortium—using “omics” approaches to explore the adaptability and resilience of coral holobionts to environmental change - Voolstra, Christian R.; Miller, David J.; Ragan, Mark A.; Hoffmann, Ary; Hoegh-Guldberg, Ove; Bourne, David; Ball, Eldon; Ying, Hua; Foret, Sylvain; Takahashi, Shunichi; Weynberg, Karen D.; van Oppen, Madeleine J.; et al. (Frontiers in Marine Science, 2015)
Human-induced environmental changes have been linked directly with loss of biodiversity. Coral reefs, which have been severely impacted by anthropogenic activities over the last few decades, exemplify this global problem and provide an opportunity to develop research addressing key knowledge gaps through ‘omics’-based approaches. While many stressors, e.g. global warming, ocean acidification, overfishing and coastal development have been identified, there is an urgent need to understand how corals function at a basic level in order to conceive strategies for mitigating future reef loss. In this regard, availability of fully sequenced genomes has been immensely valuable in providing answers to questions of organismal biology. Given that corals are metaorganisms comprised of the coral animal host, its intracellular photosynthetic algae, and associated microbiota (i.e. bacteria, archaea, fungi, viruses), these efforts must focus on entire coral holobionts. The Reef Future Genomics 2020 (ReFuGe 2020) consortium has formed to sequence hologenomes of ten coral species representing different physiological or functional groups to provide foundation data for coral reef adaptation research that is freely available to the research community.